2010
DOI: 10.1590/s0074-02762010000500006
|View full text |Cite
|
Sign up to set email alerts
|

Sylvatic foci of the Chagas disease vector Triatoma infestans in Chile: description of a new focus and challenges for control programs

Abstract: Chagas disease, caused by the protozoan Trypanosoma cruzi and transmitted by triatomine insect vectors, affects about 10 million people worldwide (Schmunis 2000) and is the third most important global parasitic disease after malaria and schistosomiasis (World Bank 1993). Because of effective vector control campaigns, the number of acute cases has decreased markedly and has been reduced to nearly zero in previously highly endemic areas of Uruguay, Chile and Brazil (Schofield et al. 2006).The Chagas disease vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 47 publications
1
56
0
4
Order By: Relevance
“…There are probably more wild foci of T. infestans in the endemic area of Chile, not necessarily within bromeliads, as shown recently. 22 Thus, it is important to continue the search for this vector, particularly in areas where there are unexplained sources of winged adults that invade houses. It is critical to study the surrounding area when these triatomines are found infected with T. cruzi, given the higher risk of transmission of Chagas disease to their inhabitants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are probably more wild foci of T. infestans in the endemic area of Chile, not necessarily within bromeliads, as shown recently. 22 Thus, it is important to continue the search for this vector, particularly in areas where there are unexplained sources of winged adults that invade houses. It is critical to study the surrounding area when these triatomines are found infected with T. cruzi, given the higher risk of transmission of Chagas disease to their inhabitants.…”
Section: Discussionmentioning
confidence: 99%
“…20 Recently, T. infestans was found colonizing wild areas in rural localities of central Chile inhabiting terrestrial bromeliads of the genus Puya spp., 21 and rock piles. 22 The bromeliad Puya spp. provides shelter to numerous small mammals, 23 similar as in other countries, where species from the genera Rhodnius and Triatoma have also been found in bromeliads, among other ecotopes.…”
mentioning
confidence: 99%
“…In addition to this important problem, in the last few years, wild foci of T. infestans have been described, mainly in the Inter-Andean Valleys and in the Gran Chaco [8,9]. This fact was also observed in Argentina, Paraguay and Chile, showing that wild T. infestans have dispersed more widely than expected [10][11][12][13][14]. In Bolivia, the epidemiological significance of wild foci of T. infestans has been stressed [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, numerous sylvatic foci have been reported, principally in two ecoregions: Bosques Secos Interandinos and Gran Chaco (Buitrago et al 2010, 2012. Moreover, discoveries of sylvatic foci in Argentina, Paraguay and Chile show that sylvatic populations of T. infestans are more widespread than initially described (Ceballos et al 2009, Bacigalupo et al 2010, Rolón et al 2011. It is worth noting that these sylvatic populations have the potential to jeopardise control efforts because of possible free insect movements between the sylvatic environment and dwellings (Noireau et al 2005, Ceballos et al 2011.…”
mentioning
confidence: 98%